Spring Succession and Vertical Export of Diatoms and IP25 in a Seasonally Ice-Covered High Arctic Fjord - Limoges, Audrey; Massé, Guillaume; Weckström, Kaarina; Poulin, Michel; Ellegaard, Marianne; Heikkilä, Maija; Geilfus, Nicolas-Xavier; Sejr, Mikael K.; Rysgaard, Søren; Ribeiro, Sofia (Frontiers in Earth Science, 2018)
The biomarker IP25 and fossil diatom assemblages preserved in seafloor sediments are commonly used as proxies for paleo Arctic sea-ice reconstructions, but how their production varies over the seasons and is exported to the sediment remains unclear. We analysed IP25 concentrations and diatom assemblages from a five-week consecutive series of sea-ice cores and compared the results with sediment trap and surface sediment samples collected at the same site in the Young Sound fjord, Northeast Greenland. Our aim was to investigate the dynamics of diatom colonization of the spring sea ice and the in-situ production of IP25. Additionally, selected diatom taxa observed in the sea-ice samples were isolated from in-ice assemblages and their lipid composition was analysed via gas chromatography-mass spectrometry. We confirm that Haslea spicula (and not the closely related species H. crucigeroides) is an IP25-producer. All three known IP25-producing taxa (Haslea spicula, H. kjellmanii and Pleurosigma stuxbergii var. rhomboides) were present in Young Sound sea ice and the low IP25 concentrations measured in the sea ice (0.44-0.72 pg mL-1) were consistent with the low abundance of these source species (0.21-9.66 valves mL-1). Total sympagic diatom production also remained very low (21-985 valves mL-1), suggesting that the fjord’s sea ice did not provide an optimal physical-chemical environment for diatoms to thrive. Temporal changes in the sympagic diatom community were also observed, with an early presence of the pelagic Thalassiosira hyperborea and subsequent dominance of pennate taxa, including Nitzschia and Navicula species, Fossula arctica and Stauronella arctica. The assemblages observed during and after the seasonal ice melt consisted primarily of Fossula arctica, Fragilariopsis oceanica, Thalassiosira antarctica var. borealis (resting spores) and Chaetoceros spp. (vegetative cells and resting spores). The seafloor sediment assemblages largely reflected the melt and post-melt planktic production and were dominated by the resting spores of the centric Chaetoceros spp. and Thalassiosira antarctica var. borealis, and the pennate Fragilariopsis oceanica, Fossula arctica and Fragilariopsis reginae-jahniae. This study documents that IP25 is produced in Young Sound, and that the weak fingerprint of sea-ice in the sediment appears to be primarily due to the limited sea ice diatom biomass.